Paraduodenal Pancreatitis: A Deceptive Abdominal Mass with Unique Histologic Findings - Jonathan Zadeh; Anthony Andreoni; Christopher Febres-Aldana; Kritika Krishnamurthy; Jyotsna Kochiyil; Cristina Vincentelli; Kfir Ben-David (Case Reports in Surgery)
Paraduodenal pancreatitis (PP) is an uncommon abdominal pathology characterized by scarring of the pancreaticoduodenal space. Diagnosis of this inflammatory process is challenging as its clinical presentation is similar to that of pancreatic cancer. Currently, no definitive radiologic or pathologic features have been established to permit diagnosis of PP without surgical resection. However, the presence of eosinophilic concretions has been reported with increasing frequency in the histologic evaluation of PP. To the best of our knowledge, these concretions are distinctive for PP and not reported in neoplasms commonly involving the pancreaticoduodenal space. Herein, we discuss the case of a 60-year-old man who was found to have PP after pancreaticoduodenectomy for a paraduodenal mass with an initially nondiagnostic biopsy. Retrospective review of the preoperative FNA samples revealed eosinophilic concretions like those found in the final surgical specimen. If the identification of eosinophilic concretions in a background of inflammatory changes was to be accepted as a diagnostic criterion for PP, patients such as ours could be spared the morbidity associated with surgical resection.